THE INFLUENCE OF LADY USHER TRUSTWORTHINESS, ATTRACTIVENESS, AND EXPERTISE ON CONSUMER PURCHASE DECISIONS AT GIIAS 2019 - Agung Satriyo, Moch. Nur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2021)
This study has a background of trustworthiness, attractiveness, and expertise affect consumer purchase decisions at GIIAS 2019. The purpose of this study is to determine and explain the influence of trustworthiness, attractiveness, and expertise individually to the purchase decisions at GIIAS 2019. This type of study is explanatory research with quantitative approach. The research location is in Surabaya, East Java, and its surroundings, one of the cities where the GIIAS 2019 was held. Samples amounted to 100 respondents who used the sampling technique used was non probability sampling. Methods of data collection used questionnaire. Analysis of the data used is descriptive analysis and multiple linear regression analysis to test the t tests of hypotheses. The results of multiple linear regression analysis can be seen that the X1 (Trustworthiness) and Y (Purchase Decision) shows t count > t table is 2,010>1,995 sig. t (0,048) t table is 2,211>1,995 or sig. t (0,030) t table is 2,318>1,995 or sig. t (0,023) <Î± = 0.05 the influence of X3 (Expertise) towards Purchase Decision is significant. The conclusion of this study was there a significant effect between trustworthiness (X1), attractiveness (X2), expertise (X3) individually to Purchase Decision (Y). Advice given from the researchers, is expected to be used as a material consideration which the parties involved in the automotive field in creating a superior brand to make it more effective and efficient in preparing and planning as well as better marketing strategies and targeted in order to improve long-term benefits for the company.Keywords: Trustworthiness, Attractiveness, Expertise, Purchase Decisions